2016
DOI: 10.1042/ebc20160025
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic inheritance of proteostasis and ageing

Abstract: Abundant evidence shows that the genome is not as static as once thought and that gene expression can be reversibly modulated by the environment. In some cases, these changes can be transmitted to the next generation even if the environment has reverted. Such transgenerational epigenetic inheritance requires that information be stored in the germline in response to exogenous stressors. One of the most elusive questions in the field of epigenetic inheritance is the identity of such inherited factor(s). Answerin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…In evolutionary terms, the transmission of the adaptive transcriptional patterns acquired throughout the parental life course in subsequent generations via the mechanism of epigenetic memory can enable the organism to better survive in potentially adverse environments [ 84 ]. In particular, it has been repeatedly reported that offspring of parents exposed to nutritional stresses exhibit altered expression of genes related to metabolic functions including those implicated in pro-longevity metabolic pathways [ 6 ]. The mechanisms potentially responsible for such inter- and transgenerational effects are currently the subject of active investigation [ 5 , 14 , 85 89 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In evolutionary terms, the transmission of the adaptive transcriptional patterns acquired throughout the parental life course in subsequent generations via the mechanism of epigenetic memory can enable the organism to better survive in potentially adverse environments [ 84 ]. In particular, it has been repeatedly reported that offspring of parents exposed to nutritional stresses exhibit altered expression of genes related to metabolic functions including those implicated in pro-longevity metabolic pathways [ 6 ]. The mechanisms potentially responsible for such inter- and transgenerational effects are currently the subject of active investigation [ 5 , 14 , 85 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…It should be taken into consideration that when discussing such effects in any species that the first generation’s primordial germ cells can be affected by in utero exposure. Thus, we must distinguish between parental effects triggered by certain environmental cues in the developing fetus, including the germline (i.e., intergenerational effects), from truly transgenerational effects induced in subsequent generations that were not exposed to the initial environmental triggers [ 6 ]. Most literature on transgenerational effects is focused mainly on maternal contribution to offspring phenotypes, while paternal effects are considered quite rare.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, recent evidence indicates that various environmental, dietary, genetic, and pharmacological interventions elicit certain epigenetic changes that can influence the aging process and define longevity in evolutionarily distant eukaryotic organisms (Dang et al, 2009; Greer et al, 2010; Li et al, 2011; Moskalev et al, 2014; Benayoun et al, 2015; Li and Casanueva, 2016; Pal and Tyler, 2016; Sen et al, 2016). Some of these epigenetic changes can be epigenetically inherited for several generations, thus they can act in a transgenerational manner to affect the rate of aging and define the lifespan of the offspring (Greer et al, 2011; Benayoun et al, 2015; Li and Casanueva, 2016; Pal and Tyler, 2016). …”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic markers and their inheritance can contribute to proteostasis-related phenotypes determined by the response to stress of the ER across generations [ 26 ]. The epigenetic markers on ER stress might contribute to metabolic diseases.…”
Section: Endoplasmic Reticulummentioning
confidence: 99%